EMBUN PAGI SWIMMING POOL ONLINE E-TICKET BOOKING INFORMATION SYSTEM - Puput Hanafi, Ariffah; Bintang Wahyuningsih, Nur; Nur Afifah, Mutia; Dwi Al Farizi, Faizal; Rosyidi, Ridhwan; Banyu Arga, Ciptaning; Saputra, Riszki; Dikza Ramadhan, Risa; Irena Yuprifany, Putri; Susanto, Edy; Regina Putri, Frestiany (Institut Teknologi Nasional Malang, 2025)
System design can be one example of the use of the internet for information processing. The design of a web-based information system media about an object can be used to introduce the object to the public or simply to make work easier. One of its uses is in the field of online e-ticket ordering because of the development of technology that can be applied to the tourism sector. Embun Pagi Swimming Pool is a private business located in Karanganyar Regency. The swimming pool is managed very manually without a system so that errors often occur in recapitulating data. In addition, the swimming pool is also not widely known by the surrounding community due to the lack of promotion and publication from the swimming pool manager. Online e-ticket ordering aims to provide convenience for swimming pool visitors in ordering tickets, besides also making it easier for managers to make sales reports and visitor reports. So it can be concluded that visitors can order tickets through the website and can find out information about the museum and make it easier to make ticket sales reports and visitor reports for managers. In this problem, the author came up with the idea of ​​​​a web-based system innovation as a publication media for an object and making it easier to do work, so the author suggests the title of the Embun Pagi Swimming Pool Online E-Ticket Ordering Information System with the Waterfall method.